(untitled) (Nigerian Journal of Physiological Sciences, 2020)
The objective of this study was to determine the effect of administration of tamsulosin on oral glucose tolerance in normal Wistar rats. Forty (40) male albino Wistar rats were selected and divided into four (4) groups of ten (10) rats each, viz, GROUP I, II, III and IV. Group I (Normal control): Distilled water (5ml/kg), Group II (Positive control): Carvedilol(800µg/kg), Group III (Tamsulosin treated): Tamsulosin (12µg/kg), Group IV (Tamsulosin treated): Tamsulosin (40µg/kg).Different treatments of Distilled water, Carvedilol and Tamsulosin were administered once every day orally for the period of six (6) weeks. After the 6th week of the study, all the treatments were withdrawn for a further 2 weeks (7th and 8th weeks). The Animals underwent 8 hours fasting. OGTT was done at baseline (0th), and then at3rd, 6th, 7thand 8th weeks. The blood glucose of all the animals was measured via tip tail incision at 0hours (pre-glucose load). Then, 2g/kg of D(+)-glucose powder dissolved in distilled water was administered to all the animals orally; after which blood samples were measured via tail tip incision at 30, 60 and 120 minutes using standard glucometer. ANOVA and Tukey Kramer post hoc test was used. The results were revealed therein. At the baseline of the study, 2nd, 3rd week, the groups of rats treated with carvedilol (positive control),tamsulosin high dose (40µg/kg) or low dose (12µg/kg) did not show any significant difference (P>0.05) in total area under the oral glucose tolerance curve compared to the normal control group and other inter group comparison. At the 6th week of the study, the group of rats treated with carvedilol (positive control), tamsulosin low dose (12µg/kg) and tamsulosin high dose (40µg/kg) revealed significantly higher values (P<0.05) of total area under the oral glucose tolerance curve compared to the normal control group. Other inter-group comparisons were not significantly different (P>0.05). At the 7th week of the study, the group of rats treated with carvedilol (positive control), tamsulosin low dose (12µg/kg) and tamsulosin high dose (40µg/kg) revealed no significant differences (P>0.05) in total area under the oral glucose tolerance curve compared to normal control group and other inter-groups comparison. At the 8th week of the study (two weeks after treatments withdrawal), only group of rats treated with carvedilol (positive control) revealed a significant higher values (P<0.05) of total area under the oral glucose tolerance curve than the normal control group. Other inter-group comparisons were not significantly different. The current study revealed that tamsulosin affects the glucose tolerance of the Wistar rats, thereby causing hyperglycemia